An Investigation of the Functional Groups and Structure Characteristics of a Polymer Blend of Polystyrene and Poly(ε-Caprolactone) Produced by Using Bis(Dibenzoylmethanato)Zirconium(IV) Chloride Catalyst - Munzirwan, Rudi; Muhammad Yusuf, Muhammad Yusuf; Utama, Erwinsyah (Universitas Negeri Medan, 2024)
Although polystyrene (PS) finds widespread use in household applications, its non-biodegradable nature raises concerns about its environmental impact. Therefore, modifying PS by blending it with a biodegradable polymer such as poly(ɛ-caprolactone) (PCL) is essential. This study focuses on investigating the functional groups and structural characteristics of PS/PCL blends. In this study, we produce polyblend using the solvent casting method. On the other hand, the PCL employed in this study was synthesized using the bis(dibenzoylmethanato)zirconium(IV)chloride (bis(dibzm)2Zr) catalyst. Next, the FTIR analysis indicates a Van Der Wall’s interaction between PS and PCL. Therefore, we did not find any absorption of new functional groups outside of the PS and PCL functional groups. Next, the XRD analysis revealed that polyblend has a more crystalline structure than PS. Meanwhile, PCL has a more crystalline structure than PS/PCL polyblend and pure PS.